Association between caregiver ability and quality of life for people with inflammatory bowel disease: The mediation effect of positive feelings of caregivers - Fang, Ning; Deng, Haijun; Fu, Tian; Zhang, Zinan; Long, Xiuyan; Wang, Xiaoyan; Tian, Li (Frontiers in Psychology, 2022)
Inflammatory bowel disease (IBD) is an incurable digestive disease. Since patients have to live with it, improving patients’ quality of life is important. Caregiver's positive feelings and closeness may have a positive effect on patients’ quality of life. We hypothesized that caregiver’s positive feeling affected patient’s quality of life through caregiver’s caring ability, and closeness might be the upstream of this chain. In this study, we conducted a single-center cross-sectional survey by questionnaire in China to tested the hypothesis. A total of 181 patient-caregiver pairs were included. The short version of the IBD questionnaire (SIBDQ), the twelve-item short-form health survey (SF-12), the Positive Aspects of Caregiving (PAC) and Capacity Scale of caregiverswere used to collect data. All the data were collected in one interview. Spearman correlation and Bootstrap method were used to analyze the data. Mediation analysisresults indicated that caregiver’s caring ability mediated the association betweencaregiver’s positive feelings and patients’ quality of life (p<0.01), which explained 34.1% of the total variation of patients’ quality of life. Mediation analysis results also revealed that patient-evaluated or caregiver-evaluated closeness had a positive effect on patients’quality of life through caregiver’s positive feeling and caregiver’s caring ability(p<0.05), which explained 2.1% and 2.3% of the variation of patients’ quality of life.Caregiver’s positive feelings were related to caregivers’ quality of life (p<0.01), but there was no significant association between caregivers’ ability and caregivers’ quality of life. In summary, our model revealed that caregiver’s positive feeling affectedpatients ' quality of life through caregiver’s caring ability.